2004
DOI: 10.33549/physiolres.930343
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Glucose Concentrations on Expression of ELAM 1, VCAM-1 and ICAM-1 in HUVEC with and without Cytokine Activation.

Abstract: Diabetes mellitus is associated with an increased prevalence of endothelial dysfunction and development of atherosclerotic vascular diseases. We demonstrate here that hyperglycemia results in the expression of adhesion molecules on endothelial cells in vitro. Incubation of human umbilical vein endothelial cells (HUVEC) in a culture medium with 11.0 mM, 16.5 mM and 22.0 mM glucose concentrations induced the expression of intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(7 citation statements)
references
References 30 publications
1
4
1
1
Order By: Relevance
“…Besides the role of CTSS in inflammatory cytokine regulation, this study determined the effect of CTSS silencing on adhesion molecules such as VCAM-1 and ICAM-1. Similar to other studies, our study showed that hyperglycemia increased the expression of VCAM-1, ICAM-1, and VEGF-1 in HUVEC cells [ 29 , 47 ]. Hyperglycemia has been shown to increase the permeability of HUVEC monolayers, which is an early pathological mechanism in the progression of diabetic vascular complications [ 48 ].…”
Section: Discussionsupporting
confidence: 91%
“…Besides the role of CTSS in inflammatory cytokine regulation, this study determined the effect of CTSS silencing on adhesion molecules such as VCAM-1 and ICAM-1. Similar to other studies, our study showed that hyperglycemia increased the expression of VCAM-1, ICAM-1, and VEGF-1 in HUVEC cells [ 29 , 47 ]. Hyperglycemia has been shown to increase the permeability of HUVEC monolayers, which is an early pathological mechanism in the progression of diabetic vascular complications [ 48 ].…”
Section: Discussionsupporting
confidence: 91%
“…3 However, the direct influence, if any, of hyperglycemia on atherogenesis remains unclear. Increased expression of vascular cellular adhesion molecules in the diabetic endothelial cell has been shown in in vitro 4 and in vivo studies. 5 Furthermore, short-term hyperglycemia promotes monocyte adhesion to rat thoracic aorta 6 and to human aortic endothelial cells.…”
mentioning
confidence: 86%
“…In HUVEC, however, high glucose culture did not show any increase in inflammation. This comes in contrast to previously reported findings in HUVEC showing significant increases in the inflammatory surface markers, ICAM1, VCAM1 and endothelialleukocyte adhesion molecular 1 (ELAM1) upon exposure to higher glucose concentrations, peaking at 16.5 mM [346][347]. Interestingly, in the study by Altannavch et [346].…”
Section: High Glucose Culture To Model Dmcontrasting
confidence: 86%